Exploration of intensive reading-listening skills through KBI media based on outdoor media investigation for students of UIN Syekh Wasil Kediri - Nurul Dwi Lestari (Universitas Muhammadiyah Malang, 2026)
Intensive reading-listening ability is a matter that needs to be optimized for students of the Indonesian Language Education Study Program at UIN Syekh Wasil Kediri. This is considering that the profile of graduates of the study program, one of which is to become novice educators in the field of the Indonesian language. This study aims to describe (1) the level of intensive reading-listening ability of Indonesian Language Education students at UIN Syekh Wasil Kediri through the use of KBI Media (Indonesian Language Rules) based on outdoor media investigations and (2) efforts to strengthen media literacy of Indonesian Language Education students at UIN Syekh Wasil Kediri. The method used in this study is mixed-methods research, combining qualitative and quantitative approaches. This study uses a Concurrent Design model. The results of the study show that, through the use of KBI Media, information is obtained about students' abilities in intensive reading and listening. Of the six indicators of intensive reading ability, one needs improvement: the ability to identify the main idea. Meanwhile, the other five indicators have met the effectiveness aspect. As for the four indicators of intensive listening ability, two need improvement: inferential listening and reorganization. KBI Media, through outdoor media investigations, provides students with real-world experiences to help them master language skills. The integration of media literacy into lectures is realized through (1) the use of digital books and articles as learning resources; (2) producing products or content on social media as lecture output, and (3) collaborative student projects on social media.